Análise dos determinantes da intenção de realizar doações monetárias para museus brasileiros - Inácio, Raoni de Oliveira (2019)
The present thesis the main object and testing one model over the intention of monetatives individuals to the museums. This thesis uses in-depth interviews and sample surveys of data, which are analyzed using structural equations. This work seeks evaluation and performance in the integration with the interpretation of museum attributes, perception of museum performance, automatic translation, identification with the museum, trust in the museum, commitment to the museum and intention to make for the museum in a theoretical model. The results show that the index of interest for the museum is preceded by the evaluation of the museum and the commitment to the museum. From the electronic report on identification with the museum; b) an emotional service influencing the museum; c) the perception of the performance of the museum influences the trust in the museum; d) an identification with the influencer without commitment to the museum; e) identification with the museum influence on the trust in the museum; f) confidence in the commitment to the museum. Among the differences between the constructs, what stands out most is between the relevance of the museum and the identification with the museum, because, the statistic was higher (0.863). As school results, the study, the implications of future research are key at the end of the work.